Comparing the effect of LINE-based and WhatsApp-based educational interventions on reproductive health knowledge, attitudes, and behaviors among Triad adolescents: A quasi-experimental study - Cecep Eli Kosasih; Tetti Solehati; Ida Maryati (Belitung Raya Foundation, Indonesia, 2024)
Background: Adolescent populations face reproductive health challenges. Persisting gaps in Triad Adolescent Reproductive Health (ARH) comprehension and risky behaviors emphasize the necessity of integrating social media apps into health education to address Triad ARH risks among youths. Teenagers commonly use WhatsApp and LINE for social media communication, and determining the effectiveness of these two apps is scarce. Objective: This quasi-experimental study aimed to investigate and compare the impacts of educational interventions delivered through WhatsApp and LINE platforms on enhancing the knowledge, attitudes, and behaviors of adolescents concerning the Triad ARH. Methods: A total of 154 senior high school students were randomly recruited from two public schools in Bandung Regency, West Java, Indonesia. These students were divided into two groups: Group A, consisting of 78 students who received material messages using LINE, and Group B, consisting of 76 students who received material messages using WhatsApp. Participants completed a pre-test prior to the intervention and a post-test one month after the intervention. Data were collected using validated questionnaires and analyzed using Chi-square and Wilcoxon tests. Results: In the LINE group, there was an average increase in knowledge from 15.68 to 20.21, attitudes from 29.05 to 59.12, and behavior from 55.95 to 64.81 before and after the intervention period (p = 0.001). In the WhatsApp group, there was an increase in knowledge from 15.16 to 19.67, in attitudes from 34.71 to 59.54, and behavior from 54.75 to 65.97 before and after the intervention period (p = 0.001). Further analysis showed no significant difference between the LINE and WhatsApp groups in increasing the average level of knowledge (p = 0.973), attitude (p = 0.682), and behavior (p = 0.067) before and after the intervention. However, it was observed that the increase in knowledge and attitude was slightly higher in the LINE group, while the increase in behavior was slightly higher in the WhatsApp group. Conclusion: This study demonstrates that educational interventions using LINE and WhatsApp both increased the knowledge, attitudes, and behavior of adolescents related to the Triad ARH. This finding is valuable, considering the popularity of LINE and WhatsApp as mobile applications. Leveraging these platforms by nurses and other healthcare professionals can significantly improve adolescents’ health, influencing their knowledge, attitudes, and behavior regarding reproductive health.